Innovative Marketing Strategies for Sustainable Tourism Development: A Literature Review - Damiasih, D. (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
Integrating innovative marketing strategies in sustainable tourism development is imperative to meet the evolving demands of modern travelers. This research explores the efficacy of experiential marketing and technology integration in promoting sustainability within the tourism industry. Employing a literature review approach, this study critically examines the existing literature on innovative marketing strategies, collaborative initiatives, and methodological advancements in sustainable tourism marketing. The findings underscore the significance of experiential marketing in fostering environmental stewardship, promoting cultural authenticity, and cultivating lasting emotional connections with tourists. Moreover, the study highlights the pivotal role of technology integration, mainly through digital platforms and big data analytics, in enhancing destination competitiveness and disseminating information about eco-friendly tourism offerings. Collaborative initiatives such as destination partnerships and community-based tourism projects are also identified as effective mechanisms for promoting sustainability and equitable tourism development. Furthermore, the research emphasizes the need for interdisciplinary collaborations, innovative methodologies, and critical engagement with power dynamics and equity issues to advance knowledge and inform evidence-based policies and practices in sustainable tourism marketing. Overall, this study contributes to a deeper understanding of the complex interplay between marketing strategies, sustainability practices, and destination outcomes in the tourism industry.